Sowing rows of prosperity through chilli farming as a family tradition - Makkar, Gurpreet Singh; Dhillon, Tarsem Singh (Indian Farming, 2024)
This article revolves around farming families who have successfully evolved a new tradition of chilli farming through generations. The article describes the journey of a few luminary farming families who reside in southwestern border district of Ferozepur, Punjab known for its fertile lands and bountiful harvests. It is about farmers who ditched away from the traditional rice-wheat cropping cycle and capitalized the qualities of innovation, determination, and hope. For these families, growing chilli is not just a means of livelihood, but a way of life now. These families have invested countless hours of passion, dedication, and hard work, done to make chilli cultivation a profitable enterprise, and the results are truly remarkable. Their journey is as inspiring as it is heartwarming. The rows of chilli transformed into a source of prosperity not only for these families but the neighbouring communities.